2016
DOI: 10.1016/j.surg.2015.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Liver-directed surgery of neuroendocrine metastases: What is the optimal strategy?

Abstract: Introduction Neuroendocrine tumors (NETs) frequently metastasize to the liver. Surgical debulking offers symptomatic relief and improved survival. However, the frequent presence of multifocal, bilobar disease and high recurrence rates introduce doubt regarding their optimal management. Parenchyma-sparing debulking (PSD) procedures (ablation, enucleation, wedge resections) may offer similar survival improvements as resection, while minimizing morbidity and preserving functional liver tissue. Methods Clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 24 publications
3
158
0
4
Order By: Relevance
“…Uptake on SSTR PET can be predictive of therapeutic response to PRRT (42), and it is likely that SSTR PET will prove to be a more accurate selection tool than 111 In-pentetreotide for PRRT, although criteria for positive disease have yet to be developed for SSTR PET. Published series reporting on surgical cytoreduction of NET liver metastases have demonstrated that, although it is not curative, it improved survival compared with historic controls (e.g., all patients with NET metastases from large national databases) (43)(44)(45)(46)(47). The conventional wisdom is that surgical debulking "sets the clock back" but does not cure patients; thus, the presence of extrahepatic disease is not necessarily an absolute contraindication.…”
Section: Clinical Scenarios and Auc Scoresmentioning
confidence: 99%
“…Uptake on SSTR PET can be predictive of therapeutic response to PRRT (42), and it is likely that SSTR PET will prove to be a more accurate selection tool than 111 In-pentetreotide for PRRT, although criteria for positive disease have yet to be developed for SSTR PET. Published series reporting on surgical cytoreduction of NET liver metastases have demonstrated that, although it is not curative, it improved survival compared with historic controls (e.g., all patients with NET metastases from large national databases) (43)(44)(45)(46)(47). The conventional wisdom is that surgical debulking "sets the clock back" but does not cure patients; thus, the presence of extrahepatic disease is not necessarily an absolute contraindication.…”
Section: Clinical Scenarios and Auc Scoresmentioning
confidence: 99%
“…Denucleation or parenchymal-sparing hepatectomy is currently the most preferable approach for many surgeons (45,46). Combining surgery and RFA or MWA may be a feasible approach for preserving postoperative liver function.…”
Section: Liver Metastasesmentioning
confidence: 99%
“…In contrast to liver metastases from other types of cancer, surgical intervention in metastatic liver disease from NENs does not necessitate an R0 resection, although this would be the optimal approach (46,47). The rationale behind this approach is that these types of metastases are not invasive, meaning that denucleation is an acceptable approach when R0 resection is not possible.…”
Section: Liver Metastasesmentioning
confidence: 99%
“…The preferred treatment of intestinal NENs is partial or multiple resection with lymphadenectomy, as a radical treatment, or palliative, cytoreductive surgery reducing the tumour mass by approximately 90% [3]. If possible, the primary tumour site should be removed, even if the disease is generalised, with concurrent resection or enucleation of the hepatic metastatic lesions [74]. Treatment of aNENs depends primarily on the tumour size and the intensity of infiltration of the primary tumour [75][76][77].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Goblet cell carcinoid, MiNEN and NEC G3 are not classified as NEN; they should be treated according to the recommendations regarding adenocarcinoma [5,32,71,76]; 8. In NENs of the appendix with hepatic metastases, the recommended management is right--sided hemicolectomy including removal of the metastases (anatomical and non-anatomical resections) [74].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%